Lung cancer associated with combustion particles and fine particulate matter (PM2.5) - The roles of polycyclic aromatic hydrocarbons (PAHs) and the aryl hydrocarbon receptor (AhR) - Holme, Jørn A; Vondráček, Jan; Machala, Miroslav; Lagadic-Gossmann, Dominique; Vogel, Christoph F A; Le Ferrec, Eric; Sparfel, Lydie; Øvrevik, Johan (Biochemical pharmacology, 2023)
Air pollution is the leading cause of lung cancer after tobacco smoking, contributing to 20% of all lung cancer deaths. Increased risk associated with living near trafficked roads, occupational exposure to diesel exhaust, indoor coal combustion and cigarette smoking, suggest that combustion components in ambient fine particulate matter (PM2.5), such as polycyclic aromatic hydrocarbons (PAHs), may be central drivers of lung cancer. Activation of the aryl hydrocarbon receptor (AhR) induces expression of xenobiotic-metabolizing enzymes (XMEs) and increase PAH metabolism, formation of reactive metabolites, oxidative stress, DNA damage and mutagenesis. Lung cancer tissues from smokers and workers exposed to high combustion PM levels contain mutagenic signatures derived from PAHs. However, recent findings suggest that ambient air PM2.5 exposure primarily induces lung cancer development through tumor promotion of cells harboring naturally acquired oncogenic mutations, thus lacking typical PAH-induced mutations. On this background, we discuss the role of AhR and PAHs in lung cancer development caused by air pollution focusing on the tumor promoting properties including metabolism, immune system, cell proliferation and survival, tumor microenvironment, cell-to-cell communication, tumor growth and metastasis. We suggest that the dichotomy in lung cancer patterns observed between smoking and outdoor air PM2.5 represent the two ends of a dose-response continuum of combustion PM exposure, where tumor promotion in the peripheral lung appears to be the driving factor at the relatively low-dose exposures from ambient air PM2.5, whereas genotoxicity in the central airways becomes increasingly more important at the higher combustion PM levels encountered through smoking and occupational exposure.
Keywords: nádorové mikroprostředí; receptory aromatických uhlovodíků; Environmental Monitoring; Diesel exhaust; Inflammation; nádory plic; Air pollution; Particulate Matter; pevné částice; monitorování životního prostředí; Lung Neoplasms; Occupational exposure; Smoking; polycyklické aromatické uhlovodíky; látky znečišťující vzduch; Tumor metastasis; Tumor promotion; Carcinogenesis; Tumor microenvironment; lidé; Humans; Genotoxicity; Tumor Microenvironment; Receptors, Aryl Hydrocarbon; Polycyclic Aromatic Hydrocarbons; Air Pollutants